2009
DOI: 10.4269/ajtmh.2009.81.475
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies of Bacterial Meningitis in Bangladesh: Results from a Hospital-Based Study

Abstract: We conducted a study at four hospitals from June 2003 to July 2005 to investigate the etiologies of bacterial meningitis in Bangladesh. A total of 2,609 patients met the clinical case definition, and 766 had cerebrospinal fluid tested by at least one of the following methods: latex agglutination, 16S rRNA gene sequencing, or real-time polymerase chain reaction for Neisseria meningitidis A and C, Streptococcus pneumoniae, and Haemophilus influenzae type b (Hib); culture results were noted from patient records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
32
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 30 publications
9
32
0
4
Order By: Relevance
“…Çalışmamızda, bakteriyel menenjit tanısı alan hastaların en sık semptomu literatürle (17,18) uyumlu olarak ateş, ardından ise meninks irritasyon bulguları ve baş ağrısı olarak bulundu.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Çalışmamızda, bakteriyel menenjit tanısı alan hastaların en sık semptomu literatürle (17,18) uyumlu olarak ateş, ardından ise meninks irritasyon bulguları ve baş ağrısı olarak bulundu.…”
Section: Discussionunclassified
“…Bakteriyel menenjitlerde BOS lökosit sayısı çeşitli çalışmalarda, 906-9455/mm 3 arasında bildirilmiş (3,16,17,19) , Gurley ve ark. (17) ise bu löko-sitlerin %80'ini PNL olarak bildirmişlerdir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, mortality reported for patients with bacterial meningitis ranges between 9 and 35% depending on the bacterium causing the meningitis, the prevalence of the different pathogens in particular populations, having a diagnosis, and the healthcare that can be provided to the patients. [4][5][6][7][8][9] Worldwide, Streptococcus pneumoniae, Neisseria meningitidis, Streptococcus agalactiae, Escherichia coli, and Listeria monocytogenes are the most frequent etiologic agents of community-acquired bacterial meningitis. [4][5][6][7][8][9] Staphylococcus aureus is the most frequent pathogen in patients that have undergone intracranial surgery.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9] Worldwide, Streptococcus pneumoniae, Neisseria meningitidis, Streptococcus agalactiae, Escherichia coli, and Listeria monocytogenes are the most frequent etiologic agents of community-acquired bacterial meningitis. [4][5][6][7][8][9] Staphylococcus aureus is the most frequent pathogen in patients that have undergone intracranial surgery. 6 Surveillance data based on cultures from eight areas participating in the US Emerging Infections Programs Network in the 1998-2007 period showed that S. pneumoniae caused meninigitis in 58% of cases and accounted for 71% of the fatalities.…”
mentioning
confidence: 99%